A comparative evaluation of the disulfur dinitride process for the visualisation of fingermarks on metal surfaces. Issue 6 (November 2019) - Bleay, S.M.; Kelly, P.F.; King, R.S.P.; Thorngate, S.G.
Abstract: The disulfur dinitride process for fingermark visualisation was first reported a decade ago, with promising results obtained for a range of materials including metals. However, the friction sensitive nature of the material and difficulty of synthesis made routine use difficult. Many of these issues have since been addressed, making equipment and chemicals available to build an understanding of how the effectiveness of disulfur dinitride compares to other fingermark visualisation processes currently used on metal surfaces. This enables more informed advice to be given on selection of processes for treatment of metal items, an area of operational interest that encompasses weapons used in violent crime and the increasing incidence in metal theft. This paper reports a comparative study into the effectiveness of disulfur dinitride, cyanoacrylate fuming, vacuum metal deposition, gun blueing and wet powder suspensions on brass, bronze, copper and stainless steel. Experiments were conducted with the surfaces exposed to a range of environments including long term ageing, water/detergent washing, acetone washing and high temperature exposure. The results indicate that disulfur dinitride is an effective process for fingermark visualisation on metal surfaces, including those exposed to adverse environments, and may offer potential improvements over existing processes for those surfaces. Further work, including pseudo-operational trials, is recommended. Graphical abstract: Unlabelled Image Highlights: Disulfur dinitride compared to other fingermark visualisation methods Fingermark recovery rates determined for metals exposed to adverse environments Disulfur dinitride develops fingermarks on metals after washing, wiping and heating (SN)x polymer microstructures formed during fingermark visualisation revealed